421 THE LIPOPOLYSACCHARIDE BINDING PROTEIN RESPONSE TO INTRATRACHEAL LIPOPOLYSACCHARIDE. (1st January 2005) - Gamble, L.; Quinton, L. J.; Happel, K. I.; Zhang, P.; Bagby, G. J.; Nelson, S.
Abstract : Lipopolysaccharide binding protein (LBP) is an acute-phase glycoprotein that facilitates lipopolysaccharide (LPS) activation of immune cells through interactions with CD14 and toll-like receptor 4. In response to conditions such as sepsis, trauma, and ARDS, LBP concentrations increase in both plasma and bronchoalveolar lavage fluid (BALF). Less is known, however, about the role or distribution of this protein in response to localized intrapulmonary infection. The purpose of our current study was to characterize the local and systemic LBP responses to intratracheal (i.t.) LPS. C3HEN mice received i.t. LPS (10 μg) and were sacrificed at 0 h, 4 h, 8 h, 24 h, and 48 h. BALF and plasma were collected at each time point and analyzed for the content of LBP and several proinflammatory cytokines, including granulocyte colony-stimulating factor (G-CSF), tumor necrosis factor α (TNF-α), and interleukin-6 (IL-6). Livers and spleens were harvested for analysis of LBP mRNA. LBP concentrations were increased in plasma by 8 h after i.t. LPS and remained elevated throughout the entire observation period. Changes in plasma LBP paralleled similar increases in liver LBP mRNA expression. TNF, G-CSF, and IL-6 were all increased in BALF following the i.t. LPS challenge. However, while the TNF response remained compartmentalized within the alveolar space, G-CSF and IL-6 levels were elevated both locally in BALF and systemically in plasma. From these data, we conclude that LBP is systemically expressed in response to i.t. LPS. Furthermore, we speculate that the systemic LBP response may be initiated in the liver by pulmonary-derived IL-6, a cytokine known to potently induce hepatic LBP synthesis.